Acute Increases in Protein O-GlcNAcylation Dampen Epileptiform Activity in Hippocampus - Stewart, Luke T. (J Neurosci, 2017)
O-GlcNAcylation is a ubiquitous and dynamic post-translational modification involving the O-linkage of β-N-acetylglucosamine to serine/threonine residues of membrane, cytosolic, and nuclear proteins. This modification is similar to phosphorylation and regarded as a key regulator of cell survival and homeostasis. Previous studies have shown that phosphorylation of serine residues on synaptic proteins is a major regulator of synaptic strength and long-term plasticity, suggesting that O-GlcNAcylation of synaptic proteins is likely as important as phosphorylation; however, few studies have investigated its role in synaptic efficacy. We recently demonstrated that acutely increasing O-GlcNAcylation induces a novel form of LTD at CA3-CA1 synapses, O-GlcNAc LTD. Here, using hippocampal slices from young adult male rats and mice, we report that epileptiform activity at CA3-CA1 synapses, generated by GABA(A)R inhibition, is significantly attenuated when protein O-GlcNAcylation is pharmacologically increased. This dampening effect is lost in slices from GluA2 KO mice, indicating a requirement of GluA2-containing AMPARs, similar to expression of O-GlcNAc LTD. Furthermore, we find that increasing O-GlcNAcylation decreases spontaneous CA3 pyramidal cell activity under basal and hyperexcitable conditions. This dampening effect was also observed on cortical hyperexcitability during in vivo EEG recordings in awake mice where the effects of the proconvulsant pentylenetetrazole are attenuated by acutely increasing O-GlcNAcylation. Collectively, these data demonstrate that the post-translational modification, O-GlcNAcylation, is a novel mechanism by which neuronal and synaptic excitability can be regulated, and suggest the possibility that increasing O-GlcNAcylation could be a novel therapeutic target to treat seizure disorders and epilepsy. SIGNIFICANCE STATEMENT We recently reported that an acute pharmacological increase in protein O-GlcNAcylation induces a novel form of long-term synaptic depression at hippocampal CA3-CA1 synapses (O-GlcNAc LTD). This synaptic dampening effect on glutamatergic networks suggests that increasing O-GlcNAcylation will depress pathological hyperexcitability. Using in vitro and in vivo models of epileptiform activity, we show that acutely increasing O-GlcNAc levels can significantly attenuate ongoing epileptiform activity and prophylactically dampen subsequent seizure activity. Together, our findings support the conclusion that protein O-GlcNAcylation is a regulator of neuronal excitability, and it represents a promising target for further research on seizure disorder therapeutics.